Macroeconomic Fundamentals and Budget Deficit Nexus: Evidence from a Developing Economy - Sanusi, Gbenga Peter (Richtmann Publishing, 2021)
The increasing budget deficit of the Nigeriaâ€™s government in the past few decades with its attendance impact on the economy is worrisome. This study examines the impacts of macroeconomic fundamentals on Nigeriaâ€™s fiscal deficit. An error correction model was specified and estimated. In terms of sign and size, the result showed that, there is an inverse relationship between budget deficit and the external reserve. This implies that an increase in the external reserve, leads to a decrease in budget deficits. A unit increase in external reserves resulted in 12.4 percent fall in budget deficit. In contrast, however, national income and interest rate showed a positive relationship with budget deficit. Increase in income expands the potential and propensity to spend. Lenders are equally more disposed to lend to the government because of the presupposed economic prosperity. The lagged value of the error correction term has the expected inverse sign of -0.42, and highly significant. The negative value of the error correction model further supports the co-integration relationship among the variables. Thus, macroeconomic variables influence budget deficits. Economic policies which minimizes macroeconomic fluctuations is paramount in curbing the negative impacts of increasing government deficit in the economy. Â Received: 27 February 2021 / Accepted: 24 May 2021 / Published: 8 July 2021